Factors Affecting Housing Prices in Malaysia Using Regression and Correlation Analysis - Kyau, Chin Wen; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2026)
Housing is a fundamental requirement of every citizen in every country. Thus, it is important to understand what factor affects housing prices. Regression and correlation analysis are the techniques used in this research to investigate the factors influencing housing prices in Malaysia. There are four identified influencing factors are examined: Gross Domestic Product (GDP), inflation rate, population and labour force. Simple linear regression is applied to study the impact of each factor individually on housing prices, whereas multiple linear regression is applied to investigate the combined effects of all factors collectively. All analyses involved secondary data ranging from year 2020 to 2024, collected from various reliable sources. Correlation coefficients, R² and significance testing are used to measure the reliability of the regression models and correlation analysis. The results show that the effects of each factor on housing prices are different, with GDP showing the strongest positive relationship. These findings can guide policymakers, investors and stakeholders in developing policies and strategies to address the Malaysian housing market effectively.